If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5p + 5 = 14 + 4p Reorder the terms: 5 + 5p = 14 + 4p Solving 5 + 5p = 14 + 4p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-4p' to each side of the equation. 5 + 5p + -4p = 14 + 4p + -4p Combine like terms: 5p + -4p = 1p 5 + 1p = 14 + 4p + -4p Combine like terms: 4p + -4p = 0 5 + 1p = 14 + 0 5 + 1p = 14 Add '-5' to each side of the equation. 5 + -5 + 1p = 14 + -5 Combine like terms: 5 + -5 = 0 0 + 1p = 14 + -5 1p = 14 + -5 Combine like terms: 14 + -5 = 9 1p = 9 Divide each side by '1'. p = 9 Simplifying p = 9
| -x+7x-7+2=29+2x+2 | | 55=-138+x | | 10b+15+6b=39 | | 4*2/10 | | (3x+4)(x+5)=0 | | 5x+31=13x-37 | | 94=88+d | | 21=3x-7(-2x+14) | | 299=-290+b | | 1/2(2x-5)=4 | | 135=60+y | | r+2=14 | | 12-3(x)=15 | | 204=-125+w | | 8x-29=5x+25 | | 8.5=8.50 | | 2.489+-4.3= | | 183=83+k | | -1/3x^2+5=0 | | ln(7x+2)=ln(5x-14) | | 21/3/8 | | 231=62+s | | 6x+68=7x+13 | | 123=-282+a | | 2(x)+9=15 | | 8(x-4)-2(x-3)+9x= | | 80=-39+c | | -6.8+-1.9= | | -113=-2x-3(-x+35) | | 3x-4=8x+16 | | 3m+v=-0.11+5v | | 2+1+f=-f+7f-2 |